2017
DOI: 10.1021/acs.jpclett.7b02998
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Enhancement by a Rapid Thermal Treatment of Nanodisk-Shaped SnS Photocathodes

Abstract: Photocathodes made from the earth-abundant, ecofriendly mineral tin monosulfide (SnS) can be promising candidates for p/n-type photoelectrochemical cells because they meet the strict requirements of energy band edges for each individual photoelectrode. Herein we fabricated SnS-based cell that exhibited a prolonged photocurrent for 3 h at -0.3 V vs the reversible hydrogen electrode (RHE) in a 0.1 M HCl electrolyte. An enhancement of the cathodic photocurrent from 2 to 6 mA cm is observed through a rapid thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 38 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…In Figure , for both SnS/FTO and SnS/ERGO/FTO interfaces, this interval was 200 mV and 150 mV, respectively. Although these intervals may seem narrow, previous report of SnS thin film show that the potential interval where Mott‐Schottky plots are linear vary between 200 and 40 mV,, confirming our results.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In Figure , for both SnS/FTO and SnS/ERGO/FTO interfaces, this interval was 200 mV and 150 mV, respectively. Although these intervals may seem narrow, previous report of SnS thin film show that the potential interval where Mott‐Schottky plots are linear vary between 200 and 40 mV,, confirming our results.…”
Section: Resultssupporting
confidence: 92%
“…The electroreduction of GO was carried out by a one electrochemical step, similar to the procedure informed by J. Basu et al …”
Section: Methodsmentioning
confidence: 99%
“…These SnS materials with a few layers have a wider optical band gap (>1.5 eV) than the corresponding bulk crystal . Owing to such a thickness‐dependent tunable band gap as well as its advantageous optical properties such as a high absorption coefficient (>10 4 cm −1 ) and a direct band gap, SnS gets great attention as an emerging material of interest for solar energy harvesting …”
Section: Introductionmentioning
confidence: 99%
“…[36,173,203] Moreover, the abundant constituent elements, excellent stability, and low toxicity compared to lead and cadmium, also make SnSbased nanostructures more promising than most other semiconductors on the basis of long-term, low-cost, and environmentally benign optoelectronic technologies. [23,25,60,78,87,103,139,[210][211][212][213][214][215] In 2020, Krishnamurthi et al [23] successfully fabricated single-layer and multilayer SnS with lateral dimensions reaching the millimeter scale by utilizing van del Waals transfer of molten Sn on conventional substrates, such as SiO 2 /Si. Figure 21a presents the schematic diagram of SnS NS-based photodetector fabricated on a SiO 2 /Si substrate.…”
Section: Optoelectronicsmentioning
confidence: 99%
“…It can also be found that a much higher photocurrent density of 2.4 mA cm À2 is also obtained after a buffer layer of CdS was inserted between SnS and TiO 2 layers due to the formation of staggered type II heterojunction. [78] Apart from these, in 2017, Patel et al [215] fabricated high-quality thickness-controlled SnS thin films on a FTO-coated glass, which exhibited a significant enhancement of the cathodic photocurrent by a facile thermal treatment. Figure 21i presents the incident photon to current conversion efficiency (IPCE) values of SnS thin film-based photocathodes measured at an applied potential ranging from 0.1 to À0.3 V versus RHE.…”
Section: Optoelectronicsmentioning
confidence: 99%